THE AESTHETICS OF BALAGHAH AND MEANING EXPLANATION IN CLASSICAL ARABIC POETRY: AN ANALYSIS OF THE QASIDA SHAUTU SHAFIRI AL-BULBULI: ESTETIKA BALAGHAH DAN PENJELASAN MAKNA DALAM SYAIR ARAB KLASIK: ANALISIS QASHIDAH SHAUTU SHAFIRI AL-BULBULI - Firmansah Setia Budi; Rohanda Rohanda; Yusuf Ali Shaleh Atha; Cahyudi Prima (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2026)
Studies on Arabic literature, particularly classical Arabic poetry, remain relatively limited within the Indonesian academic context. This condition has resulted in a low level of familiarity among students of Arabic language programs, both in Arabic Language and Literature and Arabic Language Education, with early Arabic poetry, which often leads to difficulties in understanding its meanings and linguistic aesthetics. This study aims to contribute to facilitating students’ general understanding of classical Arabic poetry, while also revealing its aesthetic dimensions through an analysis of the asalib balaghiyah contained therein. This research employs a mixed methods approach, combining qualitative analysis through a library research approach and quantitative percentage calculations. Data were collected through documentation by examining various literary sources relevant to the research theme. The results indicate that there are 22 instances of asalib balaghiyah found in the qashidah Shautu Shafiri Al-Bulbuli by Al-Ashma’iy, consisting of 8 instances of uslub majaz, 7 of uslub tasybih, 5 of uslub ithnab, and 2 of uslub kinayah. These findings demonstrate that Al-Ashma’iy tends to employ metaphorical expressions (majaz) more dominantly than other types of asalib balaghiyah in the qashidah.